Growth, biomass, and carotenoids content analysis of Navicula sp. and Chlorella sp. in batch cultures with different salinities - HASLIANTI HASLIANTI; SAHIDIN SAHIDIN; ASNANI ASNANI; ADRYAN FRISTIOHADY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Haslianti, Sahidin, Asnani, Fristiohady A. 2023. Growth, biomass, and carotenoids content analysis of Navicula sp. and Chlorella sp. in batch cultures with different salinities. Biodiversitas 24: 4299-4306. The physiological activity of microalgae is strongly influenced by culture conditions. Therefore, the rebound in this microscopic plant blooming phenomenon varies according to the aquatic environmental parameters, especially the salinity of its medium. This study aimed to analyze the cell density, biomass, and carotenoid content of two types of microalgal cultures isolated from the sea of Southeast Sulawesi. This research was conducted from October 2021 to October 2022. The independent variable in this study was salinity (30, 33, and 36‰), and the dependent variables were the parameters of cell density, biomass, and carotenoids content. This study consisted of 135 unit experiments using a completely randomized design (CRD). The same trend in cell density is observed in the two types of microalgae, where exponential growth occurred from day 2 to day 6 and decreased in growth rate on day 7. The biomass content of the two types observed was relatively the same, ranging from 0.0176-0.0181 g, while the carotenoids content ranged from 12.8294-25.5958 g/mL. The highest carotenoids level was found in the type of Chlorella sp. (25.5958 g/mL) while the lowest was in the type of Navicula sp. (12.8294 g/mL). The data indicate that the salinity parameter (>30?36‰) greatly influences and thus spikes growth in cells due to their biomass and high carotenoid content. The environment parameter also contributes significantly to other physiological parameters (one-way ANOVA, p<0.05).